Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/1475-925x-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen-rich cell culture surfaces on type X collagen expression by bovine growth plate chondrocytes

Abstract: BackgroundRecent evidence indicates that osteoarthritis (OA) may be a systemic disease since mesenchymal stem cells (MSCs) from OA patients express type X collagen, a marker of late stage chondrocyte hypertrophy (associated with endochondral ossification). We recently showed that the expression of type X collagen was suppressed when MSCs from OA patients were cultured on nitrogen (N)-rich plasma polymer layers, which we call "PPE:N" (N-doped plasma-polymerized ethylene, containing up to 36 atomic percentage (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We have detected very similar pattern of the results in mRNA expression and protein levels during PACAP administration and oxidative stress in relation to other ECM proteins such as collagen type II and aggrecan core protein [ 22 ]. The elevated presence of collagen type X in the ECM is a key event during chondrocyte hypertrophy leading to calcification of cartilage matrix [ 48 ]. It is worthy of note, that a simultaneous significant elevation of the amount of type IX collagen may reflect on certain matrix reorganization upon mechanical load.…”
Section: Discussionmentioning
confidence: 99%
“…We have detected very similar pattern of the results in mRNA expression and protein levels during PACAP administration and oxidative stress in relation to other ECM proteins such as collagen type II and aggrecan core protein [ 22 ]. The elevated presence of collagen type X in the ECM is a key event during chondrocyte hypertrophy leading to calcification of cartilage matrix [ 48 ]. It is worthy of note, that a simultaneous significant elevation of the amount of type IX collagen may reflect on certain matrix reorganization upon mechanical load.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several promising reports have suggested that it is feasible to inhibit expression of collagens type I and X to control the chondrogenic differentiation pathway of MSCs (7,115,118,154). Bian et al showed that coculture of human MSCs with human articular chondrocytes in HA hydrogels enhanced the mechanical properties and cartilage-specific ECM content of tissue-engineered cartilage.…”
Section: Improving the Structure And Functional Utilities Of Msc-basementioning
confidence: 99%
“…Petit et al showed that the extent of expression of type X collagen was reduced, at least transiently, upon growth on nitrogen-rich surfaces of both plated chondrocytes and MSCs from OA patients. This would enhance chondrogenesis (115). Rampersad et al found that growth on nitrogen-rich plasma-polymerized ethylene surfaces downregulated type X collagen expression in vitro when MSCs from OA patients were precultured on such surfaces before formation of pellet cultures.…”
Section: Improving the Structure And Functional Utilities Of Msc-basementioning
confidence: 99%
“…Furthermore, MSCs continue to express collagen type I (Steck et al 2005 ). Recently, several promising results have been published that show the feasibility of inhibiting collagen type I and X expression and thereby controlling the chondrogenic differentiation pathway of MSCs (Rampersad et al 2011 ; Petit et al 2011 ; Bian et al 2011 ; Fischer et al 2010 ).…”
Section: Important Parameters For Cartilage Tissue Engineering Studiementioning
confidence: 99%